Assessing Leader Humility. Issue 3 (1st August 2020) - Swain, Jordon E.; Murray, Elise D.
Abstract: The character strength of humility has been linked to a growing number of desirable leader-related outcomes. Consequently, academics and practitioners alike have begun to search for interventions to develop or encourage humility in leaders. But assessing humility (and the effectiveness of these interventions) has proven difficult. Measures for assessing humility do exist, but these traditional methods come with weaknesses that make them less than ideal. This article outlines the existing methods used to assess humility, discusses weaknesses in those current methods, and highlights some promising emerging assessment methods that warrant further exploration.